Photodynamic therapy in dermatology - Gold, Michael H. (Springer New York, 2011)
Photodynamic Therapy in Dermatology is the first book to cover global research on photodynamic therapy (PDT) in the management of skin disease. Although a relatively young procedure, PDT has enjoyed increased popularity during the last ten years. As research has grown, two distinct routes have appeared: the United States model and the European one, each focusing on different uses and photosensitizers. Dr. Gold has assembled the world’s experts on PDT to create a book that concisely covers every use and photosensitizer available around the world and includes comprehensive coverage of both of the FDA-approved photosensitizers in the United States, all the while carefully differentiating between off-label and FDA-approved uses of photodynamic therapy. Photodynamic Therapy in Dermatology emphasizes how to integrate PDT into practice. Toward this end, it is organized by disease category, with each chapter providing a systematic discussion of indications, PDT approaches from country to country, common side effects, prognosis as well as the underlying science. The book will be of value to dermatologists seeking a state-of-the-art review of PDT around the world, the latest in its clinical uses, and guidance on how to incorporate PDT into clinical practice. History of photodynamic therapy -- Aminolevulinic acid: actinic keratosis and photorejuvenation -- 5-Aminolevulinic acid: acne vulgaris -- Photodynamic therapy for the treatment of sebaceous gland hyperplasia -- Photodynamic Therapy for hidradenitis suppurativa -- Topical methyl aminolevulinate photodynamic therapy for the treatment of actinic keratosis -- Methyl aminolevulinate in skin cancers -- Methyl aminolevulinate: photorejuvenation -- Photodynamic therapy of acne -- Photodynamic therapy for the treatment of verrucae, condylomata acuminata, and molluscum contagiosum lesions -- Photodynamic therapy and inflammatory disorders -- Photodynamic therapy for other uses -- Chemoprevention of skin cancer with photodynamic therapy -- Fluorescence-guided photodynamic therapy -- How I perform ala-photodynamic therapy in my practice -- How we perform photodynamic therapy MAL in clinical practice -- The future of photodynamic therapy.